A taxing audit—On the association between auditor workload compression and tax avoidance. Issue 4 (3rd August 2022) - Lopez, Dennis M.; Greenwald, S. Mark
Abstract : This study investigates the association between auditor workload compression and tax avoidance. Heavy auditor workloads can limit the extent to which auditors are able to examine the determination of the income tax provision, creating opportunities for companies to maintain their tax avoidance strategies unimpeded. We find evidence indicating that audits performed by auditors with greater levels of workload compression are associated with greater levels of tax avoidance, as proxied by the cash effective tax rate, the Generally Accepted Accounting Principles (GAAP) effective tax rate and book‐tax differences. We also investigate the role of auditor‐provided tax services (APTS) on the said associations and find evidence generally consistent with knowledge spillover; however, we do not find evidence of a moderating effect from APTS on the association between auditor workload compression and tax avoidance. This study contributes to the auditing and tax literatures by being among the first to investigate whether audit‐related constraints due to workload compression affect the outcomes of management's determination of the tax provision.